The Impact of Handphone Use on Character Development of Children in Elementary School - Riski, Riski; Ain, Siti Quratul (Universitas Pendidikan Ganesha, 2022)
Uncontrolled use of mobile phones will negatively impact children's development, especially character development. Children who only focus on cellphones, such as playing games and social media, will neglect their responsibilities and discipline. This study aimed to analyze the impact of using mobile phones on the development of children's character at elementary school age, especially in the fifth grade of elementary school, using descriptive qualitative methods. The methods used to collect data are observation, interview, and documentation. The instrument used to collect data is a questionnaire. In this study, eight parents and two classroom teachers became sources of information. The technique used to analyze the data is descriptive qualitative analysis with triangulation techniques. The study results are that excessive use of cell phones impacts children. There are positive and negative impacts. The positive impact is that students can look for various sources of information and can communicate remotely with their friends. Meanwhile, the negative impacts can disrupt children's development, such as discipline, responsibility, and socializing inability. It can be concluded that excessive use of mobile phones can disrupt the development of children's character at elementary school age, especially in the fifth grade of elementary school.